Low-dose atropine for myopia progression in children: a 2017–2024 systematic review and meta-analysis of randomized placebo-controlled trials - Magurno, Luciano; Lang, Maximiliano; Zapata, Martina; Gallo, Juan E. (Frontiers in Medicine, 2026)
BackgroundLow-dose atropine (0.01%) eye drops have emerged as a proposed intervention to slow myopic progression in children, but their short-term efficacy remains uncertain. We conducted a systematic review and meta-analysis of recent randomized, placebo-controlled trials to assess the efficacy and safety of 0.01% atropine in preventing myopia progression.MethodsA comprehensive search of PubMed, Embase, and Cochrane Library (through October 2024) identified double-blind randomized trials published from 2017 to 2024 that compared atropine 0.01% with placebo in children. Primary outcomes were the changes in refractive error (spherical equivalent) and axial length over at least 1 year. Secondary outcomes included treatment-related adverse events (e.g., photophobia). Data were extracted, pooled using random-effects models, and heterogeneity was assessed (I2 statistic).ResultsNine trials (n = 1,091) met inclusion. Spherical equivalent refraction (SER): MD +0.14 D/year (95% CI +0.04 to +0.24, p = 0.01; I2 = 64%). Axial length: MD −0.05 mm/year (95% CI −0.08 to −0.01, p = 0.01; I2 = 30%). Photophobia: RR 1.17 (95% CI 0.43–3.20, p = 0.69; I2 = 15%).ConclusionAt 12 months, 0.01% atropine yields small but statistically significant reductions in the progression of spherical-equivalent refraction and axial elongation, with no statistically significant increase in photophobia versus placebo, although absolute photophobia rates were higher in the atropine group (9.8% vs. 5.9%). Effects are modest and heterogeneous, and the 95% prediction intervals include the null, supporting the need for larger, longer-term trials to define the durability and clinical relevance of these findings.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024583729.